On Quitting Rights in Mechanism Design - Compte, Olivier; Jehiel, Philippe (American Economic Review, 2007)
Quitting rights play a major role in many economic interactions, whether in the precontractual phase or after contracts have been signed. Clearly, no party can be forced to sign a contract if she is unwilling to, thus implying that quitting rights can be exerted at the ex ante stage when no contract has been signed. But, quitting rights can also be exerted after explicit contracts have been signed in a number of instances. For example, most labor contracts allow employees to leave their job if they want to. Also, quitting rights may be asymmetric across agents as labor contracts illustrate. (Employers are generally constrained in their ability to replace their employees.)